Helsingin valtaus 1918 - Kaukokallio, Urho
sisällön kuvaus: Helsingin valtaus 1918. Työväentalon tornissa on tulipalo.
Keywords: kansalaissota; työväenliike; tulipalot; Suomi, Uusimaa, Helsinki, Siltasaari Helsinki, Säästöpankinranta 6